Rational design of cathode structure based on free-standing S/rGO/CNT nanocomposite for Li-S batteries - Köse, Hilal; Şahin Kurt, Büşra; Dombaycıoğlu, Şeyma; Aydın, Ali Osman (Elsevier Science, 2020)
Sulfur / reduced graphene oxide / carbon nanotube (S/rGO/CNT) composite cathodes were fabricated as laminar-structured free-standing papers to develop high-capacity lithium sulfur batteries (Li-S). Here, the rGO content improved the electronic conductivity and acted as a buffer to accommodate volumetric expansion of sulfur together with CNTs. In this study, it was aimed to benefit from the synergistic effect of the hybrid structure of rGO and CNT, and to determine the effect of rGO and CNT ratio on the S/rGO/CNT cathode capacity. For this purpose, the free-standing, flexible and binder-less paper cathodes were rationally designed by using different rGO/CNT ratios via a vacuum filtration method. To characterize the fabricated S/rGO/CNT cathodes, thermogravimetric analysis (TGA), field emission gun scanning electron microscopy (FEG-SEM), energy dispersive x-ray spectrometer (EDS), x-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), Raman spectroscopy and electrochemical performance tests were used. In the fabrication of S/rGO/CNT cathodes, the obtained results showed that the use of 2:1 rGO/CNT ratio exhibited more mesoporous, well-designed laminar structure and higher discharge capacity according to 1:1 and 1:2 rGO/CNT ratios. As a result, the most effective cathode was achieved at 0.1C after 300 cycles, exhibiting a 701 mA h g(-1) discharge capacity. According to the obtained results, the fabricated cathode structures could be promise as novel high-performance Li-S cathode materials with a facile method.
Keywords: S/Rgo/CNT Composite Cathodes; Laminar Structure; Rgo/CNT Rational Design; Free-Standing Papers; Li-S Batteries